Jeanne Lampl-de Groot papers - Lampl-de Groot, Jeanne
Correspondence and undated speech by Lampl de-Groot relating her memories of Sigmund Freud and her thoughts on the evolution of psychoanalytic technique and theory. Correspondents include Princess Marie Bonaparte, Heinz Hartmann, Ernest Jones, and James Strachey.
Psychoanalyst.
In English and German.
Forms part of: Sigmund Freud collection.
Keywords: Bonaparte, Marie, -- Princess, -- 1882-1962 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Hartmann, Heinz, -- 1894-1970 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Strachey, James -- Correspondence; Psychoanalysis; Psychoanalysts